Pengaruh Lokasi, Ketersediaan Modal dan Risiko Terhadap Pengembangan UMKM di Kecamatan Medan Polonia: Studi Kasus UMKM Tahu dan Tempe di Kel. Sari Rejo, Kec. Medan Polonia - Annisa Fajaria; Muhammad Arif; Mawaddah Irham (MES Management Journal, 2025)
This research aims to find out and analyze how and how much Location, Capital Availability and Risk towards the development of micro, small and medium enterprises (MSMEs) in Medan Polonia sub-district (Case study of Tofu and Tempe MSMEs in Kel. Sari Rejo, Kec. Medan Polonia). The research method used in this research is a quantitative descriptive approach. The type of data used is primary and secondary. The subjects in the research were Tofu and Tempe MSMEs in Kel. Sari Rejo, Kec. Medan Polonia and the objects of this research were 32 respondents. The test tool used in this research is SPSS 20.0 to test classical assumptions, multiple regression analysis, and hypothesis testing. Based on the results of the hypothesis test, namely the t test, it shows that location has a positive and significant effect on the development of micro, small and medium enterprises (MSMEs). Capital Availability has a positive and significant effect on the development of micro, small and medium enterprises (MSMEs). Risk has a positive and significant effect on the development of micro, small and medium enterprises (MSMEs). And the results of the F test show that the Location, Capital Availability and Risk simultaneously have a significant effect on the development of micro, small and medium enterprises (MSMEs) with an F Prob value of 0.0000. The results of this test show that Location, Capital Availability and Risk variables contribute 73.9% to the development of micro, small and medium enterprises (MSMEs) variable.